2019
DOI: 10.1007/s00394-019-01964-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between long-term adherence to healthy diet and recurrent depressive symptoms in Whitehall II Study

Abstract: Purpose We examined whether long-term adherence to three diet quality scores-the Alternative Healthy Eating Index-2010 (AHEI-2010), Dietary Approach to Stop Hypertension (DASH) and transformed-Mediterranean Diet Score (tMDS), Alternative Healthy Eating Index-2010 (AHEI-2010) and Dietary Approach to Stop Hypertension (DASH) is associated with the risk of recurrent depressive symptoms. Methods Analyses were conducted on a sample of 4949 men and women from the Whitehall II study. Diet scores were calculated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…Across the whole sample of dietary patterns, a high-quality diet was associated with lower depressive symptoms. These findings align with recent research that showed a high-quality plantbased diet may protect against the onset or severity of depression [42] and that improved dietary quality, in general, is related to lowering the symptoms of depression [17,[56][57][58].…”
Section: Discussionsupporting
confidence: 90%
“…Across the whole sample of dietary patterns, a high-quality diet was associated with lower depressive symptoms. These findings align with recent research that showed a high-quality plantbased diet may protect against the onset or severity of depression [42] and that improved dietary quality, in general, is related to lowering the symptoms of depression [17,[56][57][58].…”
Section: Discussionsupporting
confidence: 90%
“…Across the whole sample of dietary patterns, a high-quality diet was associated with lower depressive symptoms. These findings align with recent research that showed a high-quality plant-based diet may protect against the onset or severity of depression [ 42 ] and that improved dietary quality, in general, is related to lowering the symptoms of depression [ 17 , 56 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 90%
“…Systematic reviews and meta-analyses have found that adherence to the MedDiet reduces the risk of depression [ see for example 95,96,97,98,99,100]. However, the Whitehall II Study could not detect an effect of the MedDiet on the recurrence of depressive symptoms [101]. Nevertheless, the SUN study, which followed individuals free of depression at baseline, found that adherence to the MedDiet (comparison of the highest vs the lowest quartile) was associated with a 25% mean reduction in depression diagnoses at two-year followup [102].…”
Section: Mood and Depressionmentioning
confidence: 99%